Biological effect and chemical monitoring of Watch List substances in European surface waters: Steroidal estrogens and diclofenac – Effect-based methods for monitoring frameworks. (15th January 2022) - Simon, Eszter; Duffek, Anja; Stahl, Cordula; Frey, Manfred; Scheurer, Marco; Tuerk, Jochen; Gehrmann, Linda; Könemann, Sarah; Swart, Kees; Behnisch, Peter; Olbrich, Daniel; Brion, Franҫois; et al.
Graphical abstract: Highlights: EU-wide diclofenac and steroidal estrogen monitoring was performed with LC-MS/MS and biotests. Low estrogenicity and partly high COX-inhibition were found in the sampled surface waters. Bioassays showed good screening function and applicability for investigative monitoring. LC-MS/MS detection of EE2 remains challenging at its predicted no-effect level of 35 pg/L. Standard addition tackled LC-MS/MS detection challenges. Abstract: rationale of the study: Three steroidal estrogens, 17α-ethinylestradiol (EE2), 17β-estradiol (E2), estrone (E1), and the non-steroidal anti-inflammatory drug (NSAID), diclofenac have been included in the first Watch List of the Water Framework Directive (WFD, EU Directive 2000/60/EC, EU Implementing Decision 2015/495). This triggered the need for more EU-wide surface water monitoring data on these micropollutants, before they can be considered for inclusion in the list of priority substances regularly monitored in aquatic ecosystems. The revision of the priority substance list of the WFD offers the opportunity to incorporate more holistic bioanalytical approaches, such as effect-based monitoring, alongside single substance chemical monitoring. Effect-based methods (EBMs) are able to measure total biological activities (e.g., estrogenic activity or cyxlooxygenase [COX]-inhibition) of specific group of substances (such as estrogens and NSAIDs) in the aquatic environment at low concentrations (pg/L). This makes them potential tools for a cost-effective and ecotoxicologically comprehensive water quality assessment. In parallel, the use of such methods could build a bridge from chemical status assessments towards ecological status assessments by adressing mixture effects for relevant modes of action. Our study aimed to assess the suitability of implementing EBMs in the WFD, by conducting a large-scale sampling and analysis campaign of more than 70 surface waters across Europe. This resulted in the generation of high-quality chemical and effect-based monitoring data for the selected Watch List substances. Overall, water samples contained low estrogenicity (0.01–1.3 ng E2-Equivalent/L) and a range of COX-inhibition activity similar to previously reported levels (12–1600 ng Diclofenac-Equivalent/L). Comparison between effect-based and conventional analytical chemical methods showed that the chemical analytical approach for steroidal estrogens resulted in more (76%) non-quantifiable data, i.e., concentrations were below detection limits, compared to the EBMs (28%). These results demonstrate the excellent and sensitive screening capability of EBMs.